Análise de dispositivos hidrológicos de infiltração com modelagem por dinâmica de sistemas aplicada em São Carlos-SP - Saran, Maria Natália (Universidade Federal de São Carlos, 2024)
During urbanization, the concern with urban drainage was insufficient, so that the effects can be observed by the increasing occurrence of floods. In an attempt to reduce these impacts in cities, flood control techniques emerge, and then compensatory drainage techniques, such as lot control techniques. In this context, one of the most common devices is the infiltration well, a structure that aims to assist in the infiltration of rainwater incident on a lot. With regard to hydrological modeling, the most used techniques for calculating the decrease in downstream flow are iteration methods, which can be solved through the implementation of numerical methods in electronic spreadsheets. However, due to the complexity of implementing these methods in this type of spreadsheet, this path is sometimes unusual, and the designer ends up seeking to implement analytical solutions, when they exist. However, if there is the possibility of solving this type of problem through the use of numerical methods, in a safe and simplified way, this can open up the range of options for resolution methods, and also, on the other hand, make the use of numerical methods with diverse applications within the area of hydrological science. Therefore, with the purpose of improving calculations, and obtaining greater ease and understanding for the hydrologist, this work sought through the fundamentals of Systems Dynamics, and with the use of Vensim Software, a way of modeling problems through a simpler and more user-friendly interface when compared to the use of electronic spreadsheets. In addition to building the hydrological infiltration model in a Systems Dynamics environment, data were collected through field experiments to calibrate the model, using a new infiltrometer, in addition to comparing results based on conditions assumed by other authors. It is considered that the model performed satisfactorily for the conditions that were analyzed.
Analysis of hydrological infiltration devices using system dynamics modeling applied in São Carlos-SP
Keywords: Poço de infiltração; Dinâmica de sistemas; Infiltração; Infiltration well; System dynamics; Infiltration; ENGENHARIAS